Pemetaan Kendala dalam Aplikasi Ekonomi Kreatif di Kota Bengkalis - Tri Handayani; Supriati Supriati (Inovbiz: Jurnal Inovasi Bisnis, 2019)
The phenomenon that occurs shows how potential Bengkalis city in terms of geographical aspects as a city that is very close to neighboring countries but from the aspect of creative economic development has not increased. This study aims to map the constraints of the creative economy industry in Bengkalis City and provide recommendations in order to improve and condition the creative economy better. The study was conducted in the city of Bengkalis by conducting a semi-structure interview with 50 respondents in order to explore the constraints faced by creative economic business actors from Administrative, Technical, Operational, and Managerial (ATOM) aspects. The results of the Technical, Operational and Managerial aspects are the majority of constraints felt by creative economy business actors. There must be a breakthrough effort that must be done by the local government, and synergy with the central government and educational institutions. Keywords: creative economic, administrative, technical, operasional, mangerial